Pengembangan Penuntun Praktikum Inquiry Based Learning pada Materi Sel dan Jaringan Tumbuhan - Nurhidayah Nurhidayah; Syamsiara Nur Nino (Universitas Sulawesi Barat, 2023)
Practicum guides have an important role in practicum activities because they can help students during the practicum process. This research aims to develop a practicum guide based on Inquiry Based Learning (IBL) in Biology Subject Material of Plant Cells and Tissues for Class XI High School Students, which is valid, practical and effective. The type of research used is Research and Development (R&D) with the development procedure using the ADDIE model which consists of 5 stages namely analysis, design, development, implementation, and evaluation. The research location is MAN 2 Polman, Matakali District, Polewali Mandar Regency, West Sulawesi. The subjects of this study were Biology teachers in class XI MIPA, which consisted of 22 students. The validation results of the Inquiry Based Learning (IBL) practicum guide using assessment sheets of media experts and material experts who were assessed by 2 expert validators obtained a result of 4.2 including the valid category. Results of practicality Inquiry Based Learning (IBL) practicum guide using teacher response questionnaires and student response questionnaires. The results of the questionnaire analysis showed that the value of the teacher's response was 90% getting the very practical category and the value of the student's response was 90.1% getting the very practical category. The results of the Inquiry Based Learning (IBL) practicum guide using test questions obtained learning outcomes of 90.9% are in the very effective category. Thus the Inquiry Based Learning (IBL) practicum guide is declared valid, practical and effective for use as teaching material